Measuring women’s disempowerment in agriculture in Pakistan - Ahmad, Nuzhat; Khan, Huma (International Food Policy Research Institute, 2016)
Pakistan performs poorly withrespect to gender equality, women’s empowerment, and other gender-related indicators. Few studies in Pakistan measure the multiple dimensions of empowerment along which women are marginalized or disenfranchised, particularly in the country’s rural areas. Even fewer studies address the gender gaps in empowerment levels of men and women. This paper calculates a Women’s Disempowerment Index to examine women’s control over production, resources, income, household decisions, and time burden. The index is based on a slightly modified methodology than that used for WEAI calculation by Alkire et al. (2012). The analysis is based on a sample of 2,090 households in the rural areas of Pakistan. Data used for the study werecollected in three rounds of the Pakistan Rural Household Panel Survey from 2012–2014 by International Food Policy Research Institute/ Innovative Development Strategies for its Pakistan Strategy Support Program. The results show low empowerment levels of only 17 percent for women in the rural areas of Pakistan. The results also show very low empowerment of women in all indicators and domains except the time burden/workload indicator. We then analyze women’s disempowerment by subsamples based on individual and household characteristics. We also calculate disempowerment levels among men and compare it to disempowerment levels among women. Comparison within the household reveals large disparities in empowerment levels among men and women. In a comparative analysis, men are found to be more empowered in domains of production, income,and autonomy. Both men and women were found to be most disempowered in access to and control over resources. The paper provides a baseline for tracking women’s empowerment over time and identifies areas that need to be strengthened through policy interventions